Dealing with adolescents' recurrent pain problems in school health care—Swedish school nurses' view. Issue 4 (11th September 2019) - Golsäter, Marie; Nilsson, Stefan; Wigert, Helena
Abstract: Aim: To explore school nurses' strategies for supporting adolescents with recurrent pain. Design: An explorative inductive qualitative design. Method: Twenty‐one Swedish school nurses were interviewed, and the interviews were subjected to content analysis. Results: The findings show that the nurses are aware that recurrent pain problems are common among the adolescents. In their attempt to support these adolescents, the nurses describe how they are striving in attempts to acquire an understanding of the adolescents' situation, to understand the cause of the pain problem and to devise strategies that can be used to help the adolescents handle the situation.